New results in the computation of output-nulling subspaces - Ntogramatzidis, Lorenzo (2016)
This paper is concerned with the problem of computing basis matrices for the fundamental output-nulling subspaces and the simultaneous computation of the associated friends that place the assignable closed-loop eigenvalues at desired locations. In particular, our aim is to show that the Moore-Laub algorithm for the computation of these subspaces was stated under unnecessary restrictive assumptions.